Social Media and Influencer Marketing Strategies in Building Sustainable Tourism Awareness in the Coastal Region of West Sulawesi - Rahmat, Rahmat Ghazali; Ariyandani, Nur; Wulandari, Futri Ayu; Irawati, Irawati; Rivai, Dian Rahmayanti (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze social media and influencer marketing strategies in building sustainable tourism awareness in the coastal areas of West Sulawesi. This research uses a qualitative case study method. The research location is West Sulawesi Province. Research informants consisted of the tourism office, tourist destination managers, tourists, and local influencers. A purposive sampling technique was used to determine informants based on certain criteria. Data were collected through in-depth interviews with informants, direct field observations, and documentation. Data were analyzed using thematic analysis with the help of NVivo software. To ensure data validity, source triangulation techniques were used. The results show that social media plays a primary promotional tool capable of shaping perceptions and increasing tourist engagement in sustainable tourism awareness. Meanwhile, influencers have proven effective in conveying sustainability messages through educational content and are able to positively influence tourist behavior. This study also revealed that community involvement is still strong in aspects of destination management, but not optimal in digital promotion. Furthermore, challenges were identified in terms of facility readiness and coordination between stakeholders. This emphasizes the importance of strategic collaboration between the government, the community, and digital actors to realize sustainable tourism awareness.